2023
DOI: 10.1371/journal.pone.0279908
|View full text |Cite
|
Sign up to set email alerts
|

The study of GSDMB in pathogenesis of psoriasis vulgaris

Abstract: Background Gasdermin (GSDM) B is a member of the GSDM family, which is a protein that may be involved in the cell pyroptosis process and is associated with inflammatory diseases. Objective To explore the correlation between GSDMB and psoriasis vulgaris. Methods Skin lesions from 33 patients with psoriasis vulgaris and 69 normal controls were collected. ELISA and Western blot were adopted to detect proteins. The HaCaT cell line was transfected with 3 sets of interfering sequence siRNA, and the mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Gsdmb and Gsdmc , expressed in human keratinocytes, were also suggested to contribute to keratinocyte differentiation and cornification (Lachner et al 2017 ). In addition to skin build-up and maintenance, gasdermins, notably Gsdmb and Gsdmd , were shown to affect T-cell differentiation and function, as well as macrophage infiltration, protecting the skin against bacterial infections and contributing to the pathophysiology of skin diseases, such as psoriasis or skin fibrosis (Liu et al 2021 ; Yang et al 2022 ; Ji et al 2023 ). Our study of the gasdermin family ( Gsdma , Gsdmb , Gsdmc , and Gsdmd ) revealed some very different scenarios regarding the conservation status of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Gsdmb and Gsdmc , expressed in human keratinocytes, were also suggested to contribute to keratinocyte differentiation and cornification (Lachner et al 2017 ). In addition to skin build-up and maintenance, gasdermins, notably Gsdmb and Gsdmd , were shown to affect T-cell differentiation and function, as well as macrophage infiltration, protecting the skin against bacterial infections and contributing to the pathophysiology of skin diseases, such as psoriasis or skin fibrosis (Liu et al 2021 ; Yang et al 2022 ; Ji et al 2023 ). Our study of the gasdermin family ( Gsdma , Gsdmb , Gsdmc , and Gsdmd ) revealed some very different scenarios regarding the conservation status of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…In the second study, the expression of GSDMB in psoriatic epidermis was decreased compared to healthy skin ( Ji et al, 2023 ). The authors of the latter study stated that decreased GSDMB in psoriasis leads to inhibition of cell proliferation and stimulates apoptosis ( Ji et al, 2023 ). Taking into account that the lack of GSDMB had been linked to decreased cell proliferation in the past ( Rana et al, 2022 ), psoriasis is known for decreased apoptosis ( Shou et al, 2021 ), and those authors observed downregulation of GSDMB, these results do not correspond to psoriasis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… [ 63 ] IFI27 Keratinocytes This study demonstrates that IFI27 is required for cell proliferation in vitro and in vivo, and that if27 may be a suitable target for the development of a novel anti-psoriasis therapy [ 70 ] SERPINB2 Neutrophils Since SERPINB2 expression is positively correlated with psoriasis severity, it may be used as a biomarker for psoriasis [ 71 ] Notch-1 Endothelial cells The Notch-ligand receptor pathway may regulate vascular dysfunction and pro-inflammatory mechanisms involved in the pathogenesis of psoriasis, suggesting that targeted blockade of this pathway may have important therapeutic implications. [ 72 ] Gasdermin B Keratinocytes This study suggests that Gasdermin B may be associated with psoriasis [ 73 ] βTrCP NF-κB Keratinocytes βTrCP is involved in the NF-κB signaling mediated-, psoriasis-related inflam-mation and represent a novel target for developing agents to treat psoriasis. [ 74 ] bFGF JNK/SAPK Endothelial cells Modulation of the JNK/SAPK signaling pathway may be a promising therapeutic approach for treating angiogenesis-related diseases [ 75 ] STC1 Keratinocytes Targeting STC1 and/or signaling molecules induced by STC1 could be a new therapeutic strategy for controlling diseases involving dysregulation of epidermal and dermal interactions.…”
Section: Discussionmentioning
confidence: 99%